Diet of smooth-coated otter Lutrogale perspicillata (Geoffroy, 1826) in the Moyar River, Western Ghats, South India - Kannadasan Narasimmarajan; Manu Thomas Mathai; Matt W. Hayward; Sonaimuthu Palanivel (Academia Biology)
Otters are constrained to aquatic ecosystems where they often perform the role of “apex” predators. Effective conservation of otters requires sufficient knowledge of their dietary resources. Our aim was to determine the diet of smooth-coated otter in the Moyar River, Western Ghats, to ensure they have sufficient nutritional resources for their conservation. Ninety spraints were examined, from which we identified sixteen fish species (six families), three crabs, one mollusc, and some insects. Cyprinidae family occurred more frequently in otter diet in the post-monsoon, winter, and summer seasons, while Cichlidae were eaten mainly in the summer (analysis of variance; F = 2.442; d.f. = 1; P = 0.2161). Smooth-coated otters specialized on fishes (98.39%), while crabs and molluscs comprised 1.39% of their diet (χ2= 28.809; d.f. = 9, P = 0.001). Fishes that were eaten were between 5 cm and 41 cm in length with Hypselobarbus micropogon, Labeo pangusia, and Hypselobarbus dubius the largest (15–41 cm), while Pethia conchonius and Cirrhinus reba were the smallest (4–8 cm). The feeding pattern of otters in the Moyar River was similar throughout the year (χ2 = 1.856; d.f. = 4, P = 0.3474). We conclude that the smooth-coated otters in the Moyar River are primarily piscivores. However, season-wise fish surveys occasionally revealed low fish diversity, and otter diet and feeding patterns did not alter significantly between seasons. It highlights the potential need for distinct conservation management aims for the fragile Moyar River habitats of the Western Ghats—a global biodiversity hotspot.